Can Highway Networks Promote Productivity? Evidence from China - Yumei Lin; Junpei Huang (Journal of Advanced Transportation)
The total mileage of highways in China ranks first in the world and constitutes an important symbol of China’s modernization. Economists, however, continue to debate whether highways always promote economic growth in every region and how to assess the impact. In this paper, we first use the OD-MATRIX method to calculate the shortest highway traveling time among 332 prefecture-level cities in China from 2000 to 2013. It is shown that the reduction of traveling time brought by highway construction significantly improves enterprise productivity. Second, to further explore the mechanism at work, we apply market potential approach to examine its effect on productivity. It is found that on average, the enhanced market potential induced by highway construction in China positively affect enterprise productivity. Finally, we calculate urban centrality via the space gravity model and conduct a sample regression according to the rank of urban centrality. Interestingly, we find that the impact of highways on productivity varies depending on cities’ degree of urban centrality. Highways have a positive impact in high-centrality cities but a negative impact in low-centrality cities. This correlation can be explained, in turn, by factors that include labor and capital flow from low-centrality cities to high-centrality cities.